A popular criminology of youth justice: youth on film - Urwin, Jessica (Routledge, 2025)
"Analysing the representation of youth crime and justice-involved children in popular fictional films, this book explores how what we see on screen contributes to the perceptions of youth justice in society, policy and practice. Putting forward the argument that fictional representations have a real-world impact on the opportunities available to children, each chapter in the book focuses on a different genre or type of film and considers the ways in which justice-involved children have been demonised, stereotyped, and harmed by their portrayal on the big screen. From James Dean and the birth of 'monstrous youth' in Rebel Without A Cause to the current, more nuanced portrayals as seen in The Young Offenders, the book examines films throughout history and across different cultures. In doing so, it demonstrates how portrayals of justice-involved children have contributed to the social understanding of what youth crime is and who is to blame for it, and highlights how we can use this knowledge to better understand and support children. By combining youth justice theory with media analysis, A Popular Criminology of Youth Justice: Youth on Film makes a novel contribution to both fields and will be of great interest to students and researchers in the areas of youth crime, youth justice, and the media"--